Design of a Contact-Type Electrostatic Spray Boom System Based on Rod-Plate Electrode Structure and Field Experiments on Droplet Deposition Distribution - Hao Sun; Changxi Liu; Yufei Li; Hang Shi; Shengxue Zhao; Miao Wu; Jun Hu (Agronomy)
Spraying is currently one of the main methods of pesticide application worldwide. It converts the pesticide solution into fine droplets through a sprayer, which then deposit onto target plants. Therefore, in the process of pesticide application, improving the effectiveness of spraying while minimizing or preventing crop damage has become a key issue. Combining the advantages of electrostatic spraying technology with the characteristics of ground boom sprayers, a contact-type electrostatic boom spraying system based on a rod–plate electrode structure was designed and tested on a self-propelled boom sprayer. The charging chamber was designed based on the characteristics of the rod–plate electrode and theoretical analysis. The reliability of the device was verified through COMSOL numerical simulations, charge-to-mass ratio, droplet size, and droplet size spectrum measurements, and a droplet size prediction model was established. The deposition characteristics in soybean fields were analyzed using the Box–Behnken experimental design method. The results showed that the rod–plate electrode structure demonstrated its superiority with a maximum spatial electric field of 2.31 × 106 V/m. When the spray pressure was 0.3 MPa and the charging voltage was 8 kV, the droplet size decreased by 26.6%, and the charge-to-mass ratio reached 2.88 mC/kg. Field experiments showed that when the charging voltage was 8 kV, the spray pressure was 0.3 MPa, the traveling speed was 7 km/h, and the number of deposited droplets was 8517. This study provides some basis for the application of electrostatic spraying technology in large-scale field operations.